Marine Energy Exploitation in the Mediterranean Region: Steps Forward and Challenges - Pisacane, Giovanna; Sannino, Gianmaria; Carillo, Adriana; Struglia, Maria Vittoria; Bastianoni, Simone (Frontiers in Energy Research, 2018)
This works aims to describe current perspectives for marine energy exploitation in the Mediterranean basin, highlighting challenges and opportunities as well as the factors that still limit its market deployment. Technologies for the conversion of Marine Energy (ME) into electricity are now ready for full-scale deployment in farms of devices, making the final step from demonstration to operability and commercial exploitation. Although marine energy is more abundant along the Atlantic and Nordic European coasts, significant resources are also available in the Mediterranean Sea, opening up new perspectives for sustainable energy production in sensitive coastal areas and for the economic development of Southern Europe. The implementation of ME converters in the Mediterranean is in fact liable to induce significant technological advancements leading to product innovation, due to the local low energy levels which impose more restrictive constraints on device efficiency and environmental compatibility. In addition, the milder climate allows the testing of concepts and prototypes in the natural environment at more affordable costs, lowering capital risks for new and innovative small and medium enterprises. Research institutions and industrial players in Mediterranean countries have already taken up the challenge, despite the numerous limiting factors that still need to be removed. In particular, the ME sector adds up to the many different traditional maritime activities and to the new ocean-related industries that are developing, potentially exacerbating the competition for the use of marine space in the Mediterranean region and threatening its environmental status. The ME sector needs therefore to design suitable instruments to involve all the relevant stakeholders in a participative public debate as to how to best manage the maritime space. As the prospective sea use patterns are rapidly changing, an adequate international legal and policy framework needs to be designed for the coherent management of sea space, and Marine Spatial Planning needs to be finally implemented by EU Member States also in the Mediterranean area. To this end, the creation of transnational clusters of stakeholders is expected be an effective catalyzer, especially as they can foster the exchange of knowledge and best practices both across European countries and between the North and the South shore of the Mediterranean basin.